College physics - Bantiilan, Monica M.; Montana, Rizalina A. (Manila, Philippines : Rex Book Store, 2009)
This book is designed...
Chapter 1. Introduction -- Chapter 2. Motion --
Includes bibliographical references and index.
Keywords: PHYSICS